REGENCY REGIONAL REGIONAL BOGOR NO. 3 OF 2013 CONCERNING SOCIAL AND ENVIRONMENTAL RESPONSIBILITY - Rivaldi, Muhamad; Trijono, Rachmat (Fakultas Hukum Universitas Djuanda, 2024)
Regional Regulation (Perda) Number 1 Bogor Regent. 3 of 2013 Regarding Social and Environmental Responsibility is a regulation issued by the Bogor City Regional Government to regulate the responsibilities of the business world in protecting the environment and carrying out social activities in the environmental sector. Objective: The main objective of this sector regulation is to ensure that every business operating in Bogor Regency is socially and environmentally responsible, and makes an active contribution to regional development and the welfare of the local community. Method: Regional regulatory system. Bogor Number 3 of 2013 is a regional regulation issued by the Bogor City Government in Indonesia regarding social and environmental responsibility. This regulation aims to explain the obligations and responsibilities of individuals, businesses and organizations related to social welfare and environmental protection in the jurisdiction of the Bogor Regent. Basic regulations of the district management system. Bogor No. 3 of 2013: Social Responsibility: This regulation most likely emphasizes the importance of the contribution of businesses and individuals to the welfare of society. This may include provisions relating to community development projects, support for local initiatives or promotion of social protection programs. environmental responsibility: Another important aspect covered in the regulations This responsibility may be environmental responsibility. This could include waste management guidelines, pollution control efforts, conservation efforts and sustainable practices to protect the environment in Bogor Regency. The requirements: District management system. Government Regulation Law Number 3 of 2013 has established special compliance requirements that must be complied with by entities operating in the Region regarding their social and environmental responsibilities. Enforcement mechanisms: There may be details regarding enforcement mechanisms established to ensure compliance with regulations. This may include sanctions for non-compliance or incentives for entities that are able to carry out their social and environmental obligations well. Obligatory reporting: These regulations may also include provisions relating to mandatory reporting, requiring companies and organizations to report regularly on your social and environmental initiatives and impacts. Monitoring and Evaluation: To ensure the effectiveness of this regulation, there may be provisions to aggregate and release the results of social and environmental initiatives undertaken by the current Bogor Regent unit. In general, the district management system. No. Bogor Decree No. 3 of 2013 plays an important role in encouraging development sustainability, fostering a culture of corporate social responsibility and environmental protection in the region. Results: Regional Regulation 3 Bogor Regency. 3 of 2013 is a regional regulation issued by the Bogor Regent Government, Indonesia. These regulations focus on social and environmental responsibility, aiming to ensure that individuals, businesses and organizations in the region meet certain standards regarding their impact on society and the environment. Basic provisions of district level regulations. Bogor No. 3 of 2013 Social Responsibility: This regulation will most likely outline an entity's obligations towards local communities, such as supporting social welfare programs, improving education or contributing to poverty alleviation efforts. Environmental responsibility: This may include environmental protection and sustainability measures, such as waste management guidelines, conservation initiatives, or regulations related to pollution control. Compliance and Enforcement: There may be provisions detailing how compliance with these responsibilities will be monitored and enforced, including possible sanctions for non-compliance. Reporting requirements: Entities subject to these regulations may be required to submit regular reports on their social and environmental activities to ensure transparency and accountability. Cooperation with authorities: This regulation can also emphasize cooperation between businesses/organizations and local governments to effectively achieve shared social and environmental goals. Impact of Bogor Regency Regional Regulation No. 3 of 2013 The implementation of this regulation can provide a number of positive social and environmental impacts in Bogor Regency: Increasing social welfare through initiatives to increase corporate social responsibility accountability. Improved environmental protection results in cleaner air, water and land. . Increase business awareness of its impact on society and the environment. Strengthen partnerships between local government organizations and private sector entities for sustainable development. In short, regional regulation no. Regional Regulation Number 3 of 2013 plays an important role in encouraging social and environmental responsibility in the region, encouraging sustainable practices that are beneficial for current and future generations.